2014
DOI: 10.1080/03079457.2014.943690
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and class 1 and 2 integrons inEscherichia colifrom meat turkeys in Northern Italy

Abstract: This study is aimed at determining the antimicrobial resistance (AMR) and the presence of class 1 and 2 integrons in 48 avian pathogenic Escherichia coli (APEC) strains isolated from meat turkeys during three sequential production cycles. Thirty avian faecal E. coli (AFEC) strains from the first cycle were also analysed. Strains were tested for AMR against 25 antimicrobials by disk diffusion test and were screened for the presence of integrons and associated gene cassettes by polymerase chain reaction followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
2
11
1
2
Order By: Relevance
“…The data presented here shows that class 2 integrons were less frequently detected 5 (2.8%). Similar data have been published for Enterobacteriaceae in Nigeria [36, 38] and elsewhere [34, 39, 40]. Ramírez et al [39], reported that unlike the widespread distribution of class 1 integron within Gram-negative bacilli, only Acinetobacter baumannii and Enterobacter cloacae harboured class 2 integrons at a high frequency.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The data presented here shows that class 2 integrons were less frequently detected 5 (2.8%). Similar data have been published for Enterobacteriaceae in Nigeria [36, 38] and elsewhere [34, 39, 40]. Ramírez et al [39], reported that unlike the widespread distribution of class 1 integron within Gram-negative bacilli, only Acinetobacter baumannii and Enterobacter cloacae harboured class 2 integrons at a high frequency.…”
Section: Resultssupporting
confidence: 73%
“…All the class 2 integrons were found in isolates that were positive for class 1. Such co-carriage has been previously published on E. coli from meat turkeys in Italy, [34].…”
Section: Resultsmentioning
confidence: 63%
“…Similarly, Marchant et al (2013) have shown resistance against sulphonamides, trimethoprim, streptomycin, chloramphenicol, amoxicillin, tetracycline and neomycin to be associated with presence of integrons. Piccirillo et al (2014) have also suggested the differences between intI1-positive and intI1-negative isolates in resistance to gentamycin, streptomycin, aminosidine, triple sulphonamides and trimethoprim combined with sulfame thoxazole to be significantly higher in intI1-positive compared with intI1-negative isolates. In contrast, Oosterik et al, (2014) have found significant relationship for the presence of Class 1 integrons and resistance to trimethoprim, sulphonamides, and tetracycline only.…”
Section: Detection Of Class 1 Integronsmentioning
confidence: 99%
“…Multidrug resistance. MDR is defined as resistance to three or more classes of antimicrobial drugs; it is commonly seen among livestock isolates of E. coli (Cheney et al, 2015;Piccirillo et al, 2014) and S. enterica (European Centre for Disease Prevention and Control, European Food Safety Authority, & European Medicines Agency, 2017;Gomes-Neves et al, 2014;Mueller-Doblies, Clouting, & Davies, 2013) in Europe. The occurrence of MDR in the latter (zoonotic) species is a focus of particular concern.…”
Section: Current Issues For Amr In Livestock Bacteriamentioning
confidence: 99%